Pandangan Islam Tentang Perubahan dan Kontribusinya Terhadap Konseptualisasi Pendidikan Islam - Irianto Setyo Wibowo, Fery (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The Islamic view of change is that change is dynamic, change is a necessity that humans themselves can try their best to make changes. The concept of change in Islam is commonly referred to as hijrah, namely the direction of human change to move from an environment that is not good to be good, from disgraceful behavior to commendable, from immoral humans to human beings with good morals. The purpose of this research is to bring change in the form of a positive impact in every line of life and of course, the world of education is also constantly changing. The method used in this study is the method of observation and in-depth reference excavation from various sources or media. The results of research on changes in Islamic education include curriculum changes, changes in teaching methods, changes in teaching materials, learning strategies and media. What is clear is that this change will bring good and benefit us all.